Droplet Barcode Sequencing for targeted linked-read haplotyping of single DNA molecules. Issue 13 (19th May 2017) - Redin, David; Borgström, Erik; He, Mengxiao; Aghelpasand, Hooman; Käller, Max; Ahmadian, Afshin
Abstract: Data produced with short-read sequencing technologies result in ambiguous haplotyping and a limited capacity to investigate the full repertoire of biologically relevant forms of genetic variation. The notion of haplotype-resolved sequencing data has recently gained traction to reduce this unwanted ambiguity and enable exploration of other forms of genetic variation; beyond studies of just nucleotide polymorphisms, such as compound heterozygosity and structural variations. Here we describe Droplet Barcode Sequencing, a novel approach for creating linked-read sequencing libraries by uniquely barcoding the information within single DNA molecules in emulsion droplets, without the aid of specialty reagents or microfluidic devices. Barcode generation and template amplification is performed simultaneously in a single enzymatic reaction, greatly simplifying the workflow and minimizing assay costs compared to alternative approaches. The method has been applied to phase multiple loci targeting all exons of the highly variable Human Leukocyte Antigen A (HLA-A) gene, with DNA from eight individuals present in the same assay. Barcode-based clustering of sequencing reads confirmed analysis of over 2000 independently assayed template molecules, with an average of 753 reads in support of called polymorphisms. Our results show unequivocal characterization of all alleles present, validated by correspondence against confirmed HLA database entries and haplotyping results from previous studies.